Pengaruh temperatur heat-treatment terhadap kekerasan dan struktur mikro paduan Al-Fe-Ni - M. Husna Al Hasa (Jurnal Rekayasa Proses, 2010)
Fuel element manufacturing includes deformation process and annealing. Annealing process will change the properties of the metal. Thermal treatment will affect the nature of mechanical, physical and thermal properties of metal. This research aims to investigate the effects of thermal treatment on the properties of the materials, especially the hardness and phase of the metal alloy. Annealing process was carried out above recrystallization temperature and below melting point of the metal, e.g. 450°C, 500°C and 550°C. The hardness of Al-Fe-Ni alloy was determined by using Vickers method. The microstructure was observed by optical microscopy and grain microstructure was analyzed by DAS method. The phase structure analysis was done based on x-ray diffraction pattern. Heat treatment at three different temperatures of 450°C, 500°C and 550°C resulted in material hardness of 53 HV, 60 HV and 55 HV, respectively. Between 450°C - 500°C, the hardness of Al-Fe-Ni increased with increasing annealing temperature. On the other hand, above 500°C, the alloy hardness decreased with increasing annealing temperature. Optical metallographic observation results showed that the microstructure tends to change along with temperature increase. The microstructure of the Al-Fe-Ni alloy showed grain structure of dendritic that tends to wane at 550°C. Diffraction pattern analysis indicated that the formation of phase tended to increase at 500°C. The x-ray diffraction pattern also showed the tendency of formation of k (NiAl3) and τ (FeNiAl9) phase at 450°C. At 500°C the tendency was to form the phase τ (FeNiAl9), θ (FeAl3) and phase k (NiAl3). Meanwhile, τ (FeNiAl9) phase was preferably to form at 550°C. It was found that in the range of observed temperature, the maximum hardness of Al-Fe-Ni alloy was obtained at 500°C.